2020
DOI: 10.3390/diagnostics10090712
|View full text |Cite
|
Sign up to set email alerts
|

Aortic Root Remodeling as an Indicator for Diastolic Dysfunction and Normative Ranges in Asians: Comparison and Validation with Multidetector Computed Tomography

Abstract: Background: The aortic root diameter (AoD) has been shown to be a marker of cardiovascular risk and heart failure (HF). Data regarding the normal reference ranges in Asians and their correlates with diastolic dysfunction using contemporary guidelines remain largely unexplored. Methods: Among 5343 consecutive population-based asymptomatic Asians with echocardiography evaluations for aortic root diameter (without/with indexing, presented as AoD/AoDi) were related to cardiac structure/function and N-terminal pro-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 39 publications
0
3
0
Order By: Relevance
“…These observations suggest that alterations of the aortic wall structure/function associated with dilatation may contribute to increased LV afterload, an important factor leading to LVH. Thus, the dilatation of the most proximal arterial segment (i.e., AR and ascending tract), in addition to being a known risk factor for aortic dissection, can be considered a sign of TOD paralleling other cardiac markers of established prognostic value (39,40). In particular, the association between aortic dilatation and LVH emphasizes the role of combined arterial-ventricular remodeling in the progression of cardiovascular continuum.…”
Section: Discussionmentioning
confidence: 99%
“…These observations suggest that alterations of the aortic wall structure/function associated with dilatation may contribute to increased LV afterload, an important factor leading to LVH. Thus, the dilatation of the most proximal arterial segment (i.e., AR and ascending tract), in addition to being a known risk factor for aortic dissection, can be considered a sign of TOD paralleling other cardiac markers of established prognostic value (39,40). In particular, the association between aortic dilatation and LVH emphasizes the role of combined arterial-ventricular remodeling in the progression of cardiovascular continuum.…”
Section: Discussionmentioning
confidence: 99%
“… 52 Utsunomiya et al 53 revealed that echocardiographic total heart calcification (THC) score, which was composed of aortic valve calcification, mitral annular calcification, and aortic root calcification, had an enhancing and independent role in forecasting the mortality and morbidity of CVD. Liu et al 54 showed that aortic root diameter (AoD) could be a useful marker to identify cardiovascular risk and heart failure (HF). The authors found that advanced age, and worse hypertension and diastolic blood pressure were associated with greater AoD.…”
Section: Discussionmentioning
confidence: 99%
“…Note that mathematical methods are widely used in various applications in cardiology, such as in the basic study of arrhythmia sources [29], correlation of cardiovascular risk markers [30], to support and optimize the relevant choices in cardiac surgery via building us mathematical models [31], and to develop novel ways of assessment of properties of the heart via ultrafast shear wave imaging based on multiphysics platform which includes modeling parts [32].…”
Section: Discussionmentioning
confidence: 99%